An Integrated Analysis of Perceived Stress, Relaxation Behaviors, and Musculoskeletal Symptoms Among Undergraduate Health Science Students - Risa Kusuma Anggraeni; Andy Sirada; Sri Gunda Fahriana Fahruddin (Window of Health : Jurnal Kesehatan, 2026)
Undergraduate health science students are exposed to academic demands, prolonged screen use, and sustained static posture, which may contribute to both perceived stress and neck–shoulder musculoskeletal symptoms. Previous student-based studies have reported that approximately one-third of university students experience moderate to high stress, while musculoskeletal discomfort, particularly in the neck and shoulder regions, affects around 40–60% of students. This study aimed to examine the associations among perceived stress, stretching and relaxation behavior, static posture duration, and neck–shoulder musculoskeletal symptoms among undergraduate health science students. This observational analytic study used a cross-sectional design involving 100 undergraduate health science students at Universitas Pembangunan Nasional “Veteran” Jakarta. Participants completed the Perceived Stress Scale, a stretching and relaxation behavior questionnaire, and the Nordic Musculoskeletal Questionnaire. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The mean age of respondents was 20.8 ± 1.2 years, and 76% were female. Neck pain and shoulder pain in the past 12 months were reported by 68% and 65% of students, respectively. Static posture for 4–8 hours per day was reported by 51% of respondents. Perceived stress was categorized as mild in 43%, moderate in 21%, and high in 36% of students. Perceived stress was negatively correlated with stretching frequency (r = -0.38, p < 0.001), and positively correlated with static posture duration (r = 0.31, p = 0.002) and neck–shoulder pain (r = 0.41, p < 0.001). Regression analysis showed that stretching frequency, static posture duration, and neck–shoulder pain were significantly associated with perceived stress and explained 43% of its variance. Perceived stress among undergraduate health science students is associated with modifiable physical and behavioral factors, particularly static posture, neck–shoulder symptoms, and stretching or relaxation behavior. Campus wellness programs should integrate posture education, scheduled movement breaks, stretching routines, and relaxation practices to support both physical comfort and psychological well-being.